Legal Framework for the Police Commissions: Current State and Prospects for Development - I. O. Sviatokum (Law and Safety)
The article deals with the current legal framework for the activities of the police commissions in Ukraine. These bodies, established under the 2015 Law of Ukraine “On National Police”, are tasked primarily with ensuring transparent staffing of the police by conducting competitive selection of the candidates for the positions in the police. They include representatives from the Ministry of Internal Affairs, National Police as well as representatives of the civil society, appointed on the by the oblast councils on the local and by the Verkhovna Rada Human Rights Ombudsperson on the countrywide level. However, in the study, a number of problems of the existing regulations have been identified.